Prevalence and predictive factors associated with stunting in preschool children in a governorate of Iraq: a community-based cross-sectional study - Mhamad, Huda J.; Najmadden, Zana B.; Hama Salih, Kaihan H.; Hama, Dlkhwaz A.; Abdullah, Hiwa O.; Hasan, Karzan M.; Kareem, Honar O.; Mohammed, Bilal A.; Fattah, Fattah H.; Abdalla, Berun A.; Kakamad, Fahmi H.; Mohammed, Shvan H. (Frontiers in Nutrition, 2024)
The required data for the study was collected through a A specific structured questionnaire form was designed to collect the required data on children from their the children's parents, parents. Then, the height and weight of the children were measured.and anthropometric measurements of height were done for them. In accordanceAccording with to the World Health Organization Child Growth Standards and using the WHO Anthro Survey Analyser software, children were classified as "stunted" when their height-for-age zscore was below two standard deviations.A total of 646 children were included, of which 310 (48%) were male and 336 (52%) were female. The gestational age of 556 (86%) children was 9 months, while 84 (13%) were born between 7-9 months, and 6 (1%) were born in 7 months. With regard toRegarding feeding during the first 2 years of life, 229 children (35.4%) were exclusively breastfed, 93 (14.4%) were bottle-fed, and 324 (50.2%) had mixed feeding. The prevalence of stunting was 7.9% in the sample pool, with 4.6% of females and 3.3% of males. Among stunted children, 6.35% were term babies, and 1.55% were preterm babies. None of the studied factors had a significant association with stunting.Female gender was significantly associated with stunting (p-value <0.05).The prevalence of stunting in the studied population was 7.9%. However, we could not find any significant association between the studied factors and stunting. Thus, the factors that may significantly affect stunting in our area of study, especially the historical chemical warfare side effects, need to be more extensively investigated in future studies.The prevalence of stunting in the studied population was 7.9%, and girls were more prone to be affected by the condition, while other factors need to be more extensively investigated in future studies.